Soft dielectric elastomer microactuator for robot locomotion - Farah Afiqa Mohd Ghazali; Wong Yi Jie; Mariatul Rawdhah Ahmad Fuaad; Mohamed Sultan Mohamed Ali (Institute of Advanced Engineering and Science, 2020)
This paper presents dielectric elastomer actuated robot locomotion and the development of a robotic model structure based using a dielectric elastomer actuator. A pre-stretched dielectric elastomer actuator is fabricated onto acrylic frames to form single and multiple robotic crawler models. The crawler models demonstrate forwards motion upon application of high voltage to the attached dielectric elastomer actuator. Characterizations revealed that the fabricated multiple crawler models showed results over the single crawler model in terms of locomotion potential. The maximum forward locomotion speed of the multiple crawler models is recorded as 1.2 mm/s. Nonetheless, precise results are highly attainable provided a structured and coherent fabrication technique of the dielectric elastomer actuator is implemented.